Efficient Energy Recovery from Bamboo Leaves Waste: Graphite and Graphene Oxide Electrodes in Double Chamber Microbial Fuel Cell Configuration - Amir Maina, Butit (University Malaysia Sarawak, 2025)
Microbial Fuel Cells (MFCs) offer a sustainable method for generating electricity by utilizing bacteria to convert organic waste into energy. This research explores the use of bamboo leaves, an abundant renewable resource in Malaysia, as a substrate in MFCs, with a focus on enhancing energy recovery from bamboo leaves using graphite and graphene oxide electrodes. Microbial Fuel Cells (MFCs) face substantial limitations in achieving stable and efficient power output, which restricts their broader application. The inherently low and unpredictable power generation of MFCs often fails to meet practical energy demands, especially in rural and remote areas where reliable energy is essential. These challenges are compounded by inefficiencies in microbial. The main aim is to (i) to investigate the impact of different bacterial sources on the performance of MFCs (ii) to evaluate the relationship between bamboo leaf concentrations and MFC output and formulate strategies to optimize substrate use for peak energy efficiency and (iii) to compare and assess the effectiveness of graphite versus Graphene Oxide electrodes, with a focus on advancing MFC design through innovative engineering. The system configured as MFC contains two chambers as anode and cathode, and bamboo leaf is used as substrate. The electrodes that are used in this experiment were made of Fabricated Graphene Oxide electrode and graphite. The study found Effective Microorganisms (EM) to be more efficient than Chicken Manure (CM), achieving a higher power density of 98.37 x 10^-5 W/m² in open circuits. Graphene oxide electrodes outperformed graphite, with a peak power density of 32.3 x 10^-5 W/m² in closed circuits using EM, due to better conductivity and surface area. These findings highlight the importance of optimizing bacterial sources and electrode materials for improved MFC efficiency